Inside the role of dean international perspectives on leading in higher education - Clift, Renee T.; Loghran, John; Mills, Geoffrey E.; Craig, Cheryl J. (Routledge, 2015)
Despite deans playing critical roles in education, little is known about the knowledge, skills and dispositions needed for the job, or the practical dilemmas they face on an almost daily basis. Inside the Role of Dean offers insights into the transition of being dean, managing the daily demands and expectations of the role, and also what it means to exit such a position. This book brings being a dean and the leadership inherent in the role into sharp focus based on international perspectives on doing the job. The authors explore the nature of the system and the distinctiveness of some of the circumstances in which deans are embroiled in order to illustrate how deaning is impacted by resources and policy shifts, as well as professional and institutional expectations. They present authentic data-based accounts of what it means to be a dean through balanced and multidimensional accounts of what deans can and cannot do, the constraints they face and the opportunities tey creat with and for their faculty. -- from back cover.